Behavior of steel cross members with metallic damper under a monotonic loading effect. (August 2021) - Balik, Fatih Suleyman; Bahadir, Fatih; Emir, Furkan
Abstract: In the experimental study, it has been the main idea of this study to prevent buckling in the cross member under the effect of pressure load by placing a metallic damper at one end of the traditional tube cross-section cross members. In line with this idea, six test specimens were produced, and the specimens were tested under the pressure load effect (monotonic loading). In the testing of the specimens produced in 1/4 scale, dampers with the slotted steel plate were used for the two specimens and the bolted metallic dampers were used for the other two specimens. In order to make a comparison, tests were conducted without using any dampers at the ends of the steel cross members of two specimens. Another variable in the experiments was that the steel cross members were formed from profiles with two cross-sections. Because of the study, it has been observed that the dampers formed at the ends of the steel cross members contribute positively to the energy consumption properties of the specimens and to prevent buckling. Furthermore, it was concluded that by changing the details of the dampers used, the contribution of the specimens to the strength and rigidity properties could be increased.